Regulation of Stem Cell Populations by microRNAs - Mathieu, Julie (2013)
miRNAs are small non-coding RNAs that have emerged as crucial post-transcriptional regulators of gene expression. They are key players in various critical cellular processes such as proliferation, cell cycle progression, apoptosis and differentiation. Self-renewal capacity and differentiation potential are hallmarks of stem cells. The switch between self-renewal and differentiation requires rapid widespread changes in gene expression. Since miRNAs can repress the translation of many mRNA targets, they are good candidates to regulate cell fates. In the past few years, miRNAs have appeared as important new actors in stem cell development by regulating differentiation and maintenance of stem cells. In this chapter we will focus on the role of miRNAs in various stem cell populations. After an introduction on microRNA biogenesis, we will review the recent knowledge on miRNA expression and function in pluripotent cells and during the acquisition of stem cell fate. We will then brie fly examine the role of miRNAs in adult and cancer stem cells.